Carotid access for transcatheter aortic valve replacement: A meta‐analysis. Issue 4 (5th September 2020) - Sharma, Sharan Prakash; Chaudhary, Rahul; Ghuneim, Angela; Harder, William; David, Shukri; Choksi, Nishit; Kondur, Snigdha; Kambhatla, Swathi; Kambhatla, Sujata; Kondur, Ashok
Abstract: Objective: We sought to evaluate the feasibility and safety of carotid access transcatheter aortic valve replacement (TAVR) by performing a meta‐analysis of published cases. Background: Several case series and regional data have provided initial basis for carotid access TAVR in patients with prohibitive femoral approach. We performed this meta‐analysis to provide further evidence of feasibility and safety of carotid TAVR. Methods: We searched PubMed, EMBASE, CINAHL, and Cochrane CENTRAL for any study on carotid access TAVR involving ⩾5 patients since inception till March 1, 2020. Random‐effects model was used to compute overall effects. The outcomes analyzed were all‐cause mortality, Transient ischemic attack (TIA)/stroke, need for permanent pacemaker (PPM) implantation, pericardial tamponade, access site complications, major bleeding, and length of stay. Results: There was a total of 17 retrospective studies ( n = 2082) with a median follow‐up of 1 month. Mean age of the patient was 80 years. Mean Euroscore and STS scores were 15 ± 6.2 and 7.9 ± 3.3, respectively. The procedural success rate was 99%. The rate of all‐cause mortality was 6.7% (range 4.6–9.7%, p < .001, I 2 = 67%). Incidence of TIA/stroke was 3.9% (range 3.1–4.8%, p < .001, I 2 = 0%) and PPM implantation was 16.7% (range 12.5–21.9%, p < .001, I 2 = 56%). Rate of pericardial tamponade, vascular complication, and major bleeding were 1.7, 2.5, and 7%, respectively. Average length of hospital stay was 7.7 days. Conclusion: Our results show that transcarotid approach is a feasible option in patients with prohibitive femoral access for TAVR.